A New Lucas Operational Matrix of Fractional Derivatives Provides Spectral Solutions for Fractional Differential Equations - Vikash, Mahender Singh Poonia (Mathematical Statistician and Engineering Applications, 2023)
This exposition is partitioned into two sections. The partial subordinate of the functional grid of the Lucas polynomials is processed in the primary area. A ghastly procedure is developed and exhibited utilizing this network to address a couple of partial request starting worth issues. The subsequent segment centres around a three-sided lattice whose parts are joined likewise to frame the main request subordinate of the old style Fibonacci numbers at x=1, and whose coefficients are relating in the development of the subsidiary of Fibonacci polynomials.